Trade Barriers and Exports between Western Balkan Countries - Jusufi, Gezim; Bellaqa, Bashkim (Naše gospodarstvo/Our economy, 2019)
The aim of the paper is to identify the trade barriers imposed by the Western Balkan countries. All barriers, whether tariff or non-tariff, undoubtedly impede the normal development of trade between countries. Therefore, the paper examines merchandise trade patterns in the Western Balkan region and tries to identify the main drivers of and obstacles to intra-regional trade. Intra-regional trade comes second in importance, after trade with the European Union (EU); it underperformed and was in decline in the last few years. In the region with political challenges as the Western Balkans, non-tariff barriers significantly reduce trade exchanges between the countries in this region. Currently, the trade and political disputes (tax rate 100%) between Kosovo and Serbia showed that the imposed tariffs in trade created a political reaction between the countries, interrupting the dialogue between these countries. The originality and value of the paper are reflected in its dealing with such topics as trade barriers, genesis in ethnic and political disputes that are prominent in the Balkan region.